Analyses of N-Terminal pro-brain natriuretic peptide, cardiac troponin T, and creatine kinase MB in pericardial fluid in sudden cardiac death caused by ischemic heart disease - Zhipeng Cao; Tianqi Wang; Shao-Huang Wu; Zihan Liao; Baoli Zhu; Rui Zhao (Wolters Kluwer Medknow Publications, 2022)
Background: Biochemical analyses of N-terminal pro-brain natriuretic peptide (NT-proBNP), cardiac troponin T (cTnT), and creatine kinase MB (CK-MB) have been reported to be valuable for the auxiliary diagnosis of sudden cardiac death (SCD) in previous forensic studies. Aims and Objectives: The present study aimed to evaluate the diagnostic efficiency of combined analyses of NT-proBNP, cTnT and CK-MB in the pericardial fluid for forensic diagnosis of SCD caused by ischemic heart disease. Materials and Methods: Levels of NT-proBNP, cTnT, and CK-MB in the pericardial fluid of 132 medicolegal autopsy cases were obtained through electrochemiluminescence method. Results: NT-proBNP, cTnT, and CK-MB levels were significantly elevated in SCD cases (P < 0.05). Receiver-operating characteristics (ROC) analysis showed that NT-proBNP, cTnT, and CK-MB have diagnostic value for the diagnosis of SCD: NT-proBNP, cutoff value of 2236 pg/ml; cTnT, cutoff value of 199.51 ng/ml; CK-MB: cutoff value of 2742.5 ng/ml, and the combined analyses of these three biomarkers have better diagnostic efficiency than each single biomarker alone. Moreover, the causes of SCD were sub-divided into acute ischemic heart disease, acute myocardial infarction (AMI), and recurrent myocardial infarction subgroups for further analysis, which revealed that the ratio of cTnT/CK-MB could be used to distinguish AMI with the cutoff value of 0.1085 estimated by ROC analysis. Conclusion: These observations suggested that the postmortem biochemical analyses of NT-proBNP, cTnT, and CK-MB in the pericardial fluid may assist to diagnose SCD in forensic practice, and the combined analyses of multiple biomarkers have better diagnostic efficiency than each single biomarker alone. On the basis of the postmortem biochemical analyses of NT-proBNP, cTnT and CK-MB, combining the ratio of cTnT/CK-MB could be used to distinguish AMI.